Quality of life of patients with end-stage renal disease during initial treatment - LV Qing-na; ZHANG Xin-yu; HAN Wei; ZHANG Yan-yun; LI Yan-yan; LIU Qi-gui; REN Xian-long; YIN An-chun; SHI Tie-ying; LI Ping; XING Wei; YANG Yue (Linchuang shenzangbing zazhi)
Objective To explore and compare the effects of hemodialysis（HD） vs.peritoneal dialysis（PD） of the quality of life of patients with end-stage renal disease（ESRD）.Methods Sixty cases of ESRD receiving initial PD（PD group,n = 30） or HD（HD group,n = 30） were surveyed by the questionnaire procedure.Kidney disease quality of life short form(KDQQL SFTM Version 1.3 was used.The forms were distributed per month for consecutive 8 months.There were 480 questionnaires in total,in which valid questionnaires were 480,with the effective rate being was 100%.Results（1）SPL was continuously increased with time with the correlation being statistically significant（P =0.0000）.HD group got the maximum value for 2 groups at the sixth and seventh month after constant increases,and thereafter the value basically remained unchanged.PD group reached the maximum value at the eighth month after stable increases.（2） Effects of kidney disease（EKD） varied with the time with the correlation being statistically significant（P = 0.018）.PD group got the maximum value for 2groups at the third and fifth month after constant increases and the value was basically the same after that HD group reached the maximum value at the eighth month after stable increases.（3） Sleep patterns increased over time with the correlation being statistically significant（P = 0.029）.HD group got the maximum value for 2 groups at the sixth month after constant increased,and the value was basically the same after that PD group got the maximum value at the third month after stable increases.（4） Physical function（PF） increased over time with the correlation being statistically significant（P =0.0000）.HD group reached the maximum value for 2 groups at the sixth and eighth month after constant increases.PD group got the maximum value at the sixth,seventh and eighth month after significant increases.（5） Vitality（VT） changed over time with the correlation being statistically significant（P = 0.0000）.The VT values in both groups were constantly increased,and got the maximum at the third month and then decreased significantly after that Conclusions In the initial treatment,we can provide the correct guidance and help patients with ESRD to choose the more reasonable and feasible methods of dialysis,according to the patient’s personal situation and family social condition.